Effect of transverse rumble strips on traffic flow fundamental diagram - Torkzadeh, Ali (2013)
The purpose of this research project is to determine the effect of Transverse Rumble Strips (TRS) on the traffic flow fundamental diagram. To achieve this goal, firstly segment KM14.3-14.6, Northbound PLUS Expressway E2, which connect Johor Bahru to Kuala Lumpur had been chosen as a study area, because in this place TRS was deployed on pavement. To find traffic flow fundamental diagrams before and at TRS required data which were traffic volume, speed and density had been collected before TRS with SSD distance to avoid from the effect of TRS on traffic flow characteristics and at TRS. Required data before TRS were collected by ATC method (pneumatic tubes) and data on TRS had been collected by video camera. After installing ATC, data collected for two weeks and peak period was determined. Heaviest traffic was on Friday and Saturday during 2:00pm to 5:00pm for this reason at Friday 31 August 2012 and Saturday 1 September 2012 during 3:00pm to 4:00pm required data had been collected by a video camera on TRS. In the last step fundamental diagram for both cases before and at TRS were founded and compared with each other. This study shows that TRS in speed-density and speed-flow diagrams reduces free flow speed between 4 to 5 km/hr which is significant. But about jam density and maximum flow there was not any accurate result achieved in flow-dansity and other diagrams.